A potential link between aberrant expression of ECRG4 and atrial fibrillation - Zhang, Zuojing; Wang, Wei; Zhang, Yuxin; You, Xingji; Wu, Jingxiang (Frontiers in Oncology, 2023)
Esophageal cancer-related gene-4 (ECRG4), a 148-amino acid propertied and new tumor suppressor, is initially cloned from the normal esophageal epithelium. ECRG4 was found to be expressed not only in esophageal tissues but also in cardiomyocytes. Previous studies demonstrated that ECRG4 is constitutively expressed in esophageal epithelial cells, and its degree of downregulation is directly proportional to prognosis in patients with esophageal cancer. In the heart, ECRG4 shows greater expression in the atria than in the ventricles, which accounts for its heterogeneity. Downregulation of ECRG4 expression level correlates with esophageal cancer, as well as myocardial injuries and arrhythmias. As a result, this review summarizes the possible susceptibility gene, ECRG4 and its associated molecular mechanisms in cancer patients with atrial fibrillation and myocardial injury. The review begins by describing ECRG4’s biological background, discusses its expression in the cardiovascular system, lists the clinical and animal research related to the downregulation of ECRG4 in atrial fibrillation, and focuses on its potential role in atrial fibrillation. Downregulation of ECRG4 may increase the risk of atrial fibrillation by affecting ion channels, MMPs expression and inflammatory response. We will then discuss how ECRG4 can be used in the treatment of tumors and arrhythmias, and provide a novel possible strategy to reduce the occurrence of perioperative cardiovascular adverse events in patients with tumors such as esophageal cancer and gastric cancer.